Rectal Cancer Diagnosed after Cesarean Section in Which High Microsatellite Instability Indicated the Presence of Lynch Syndrome - Tomohiro Okuda; Hiroshi Ishii; Sadao Yamashita; Sakura Ijichi; Seiki Matsuo; Hiroyuki Okimura; Jo Kitawaki (Hindawi Limited, 2015)
We report a case of rectal cancer with microsatellite instability (MSI) that probably resulted from Lynch syndrome and that was diagnosed after Cesarean section. The patient was a 28-year-old woman (gravid 1, para 1) without a significant medical history. At 35 gestational weeks, vaginal ultrasonography revealed a 5 cm tumor behind the uterine cervix, which was diagnosed as a uterine myoma. The tumor gradually increased in size and blocked the birth canal, resulting in the patient undergoing an emergency Cesarean section. Postoperatively, the tumor was diagnosed as rectal cancer with MSI. After concurrent chemoradiation therapy, a lower anterior resection was performed. The patient's family history revealed she met the criteria of the revised Bethesda guidelines for testing the colorectal tumor for MSI. Testing revealed that the tumor did indeed show high MSI and, combined with the family history, suggested this could be a case of Lynch syndrome. Our findings emphasize the importance of considering the possibility of Lynch syndrome in pregnant women with colorectal cancer, particularly those with a family history of this condition. We suggest that the presence of Lynch syndrome should also be considered for any young woman with endometrial, ovarian, or colorectal cancer.